(3GdefgL GdJcfhdhLj h JcfhdhLjG GdJYdje h GdeYdheGJ aj GdJQHjI GdQjGVjIs - (3eUWai eMeO GdSGjMs ((3GdGScfOQjIs (3OGQ GdhaGA dOfjG GdWHGYI h GdfTQs, 2004)
(3GdefgL h GdHQfGeL GdJcfhdhLj GdeWHb aj GdeDSSGJ GdJYdjejI, h jhVM eaGgje JcfhdhLjG GdJYdje h GdhSGFd GdJYdjejI GdeSJNOeI aj GdeLGd GdQjGVj h YdGbJgG HJOQjS GdJQHjI GdQjGVjI , eHjfG OhQ GdhSGFW GdeJYOOI aj JhUjd GdeYdheGJ deYdej GdJQHjI GdQjGVjI(B.s
Keywords: (3GdJQHjI GdQjGVjI (B_(3GSGdjH GdJOQjSs; (3JcfhdhLjG GdJYdjes